Utilization of Azolla Pinnata as Compost Fertilizer on the Growth and Production of Sweet Corn (Zea mays sacchara L.) - Ajang Maruapey; Mira Herawati Soekamto; Samra Kella (Median : Jurnal Ilmu Ilmu Eksakta, 2022)
The purpose of this study was to determine the use of Azolla pinnata as compost on the growth and production of sweet corn. This research was conducted in Klamana Village, East Sorong District, Sorong City from April to June 2018Keywords: Compost, azollah pinnata, sweet corn. The study used a Randomized Block Design (RAK) which consisted of four treatments, namely; G0 = no treatment, G1 = Azolla pinnata compost treatment 1.5 kg/plot, G2 = Azolla pinnata compost treatment 3.0 kg/plot, G3 = Azolla pinnata compost treatment 4.5 kg/plot. Each treatment was repeated three times so that there were 12 experimental plots. The research data were analyzed using analysis of variance (Anova), if they were significantly different, the LSD test method was 0.05%. The results showed that the compost treatment of Azolla pinnata had a significant effect on the growth and production components of sweet corn. The treatment with a dose of 4.5 kg/plot affected the observation of plant height and number of leaves at age 8 (MST) as well as male flowering age. While the treatment dose of 3.5 kg/plot or 10 t/ha is considered better because it can increase the yield component and production of the highest cob of 3.76 kg/plot and 8.26 t/ha.